'Real world' effectiveness of the Falls Management Exercise (FaME) programme: an implementation study. (3rd February 2021) - Orton, Elizabeth; Audsley, Sarah; Coupland, Carol; Gladman, John R F; Iliffe, Steve; Lafond, Natasher; Logan, Philippa; Masud, Tahir; Skelton, Dawn A; Timblin, Clare; Timmons, Stephen; Ward, Derek; et al.
Abstract: Background: Falls incidence increases with age alongside declines in strength and balance. Clinical trials show that the Falls Management Exercise (FaME) programme improves strength and balance, which can reduce falls and improve physical functioning. Objective: To determine if the clinical trial efficacy of FaME translates into effectiveness in non-research settings. Design and setting: An implementation study of FaME in 10 local authorities across the East Midlands region of England. Subjects: Adults aged 65 and over enrolled on a FaME programme. Method: Anonymised outcome data collected by the FaME providers were compared at baseline, end of programme and 6 months follow-up using univariate and multivariate analyses. Results: For 348 adults enrolled in programmes and analysed, the mean age was 76.8, 73% were female and 143 (41%) completed ≥75% of classes. Overall confidence in balance, fear of falling, functional reach and timed-up-and-go (all P  < 0.001), and turn 180° ( P  = 0.008) improved significantly at programme completion versus baseline, but improvements were not maintained 6 months later. Falls risk (FRAT score) and total minutes of physical activity did not change significantly though minutes of strength and balance activity increased by 55% at programme completion and was maintained at 6 months. The falls incidence rate ratio (IRR) was non-significantly lower at programme completion (IRR 0.76, 95% Confidence Interval (CI) 0.48, 1.21) and follow-up (IRR 0.82 95% CI 0.48, 1.39) versus baseline. Conclusions: There is modest translation of FaME efficacy into effectiveness, but not all effects persist after completion. Strategies to aid adherence and exercise maintenance are important to maximise benefits.